Development and promise of a vocabulary intelligent tutoring system for Second-Grade Latinx English learners. Issue 2 (3rd April 2021) - Baker, Doris Luft; Ma, Hao; Polanco, Paul; Conry, Jillian Marie; Kamata, Akihito; Al Otaiba, Stephanie; Ward, Wayne; Cole, Ron
Abstract: We examine the promise, usability, and feasibility of an intelligent tutoring system (ITS) to improve the vocabulary and language proficiency in science and social studies of Latinx second grade English learners (ELs). Participants were 217 ELs attending English only programs or bilingual programs. Findings from the clustered randomized control trial using a researcher-developed proximal assessment indicated that students who used the ITS significantly improved their vocabulary knowledge of the words taught compared to students in the comparison group (ES = 0.38). Results also indicated that most students enjoyed using the ITS and learning new words. Teachers found the program feasible and beneficial to their students.